2018
DOI: 10.1177/1753193417753261
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of deformities of the radius and ulna in congenital proximal radioulnar synostosis

Abstract: We reconstructed three-dimensional images of radius and ulna in 38 forearms of 25 patients with congenital proximal radioulnar synostosis from their computed tomographic studies. We also analysed correlations between the deformities of radius and ulna and degrees of fixed pronation of these forearms. The average ulnar deviation, flexion and internal rotation deformities of the radius were 6°, 3° and 18°, respectively. The average radial deviation, extension and internal rotation deformities of the ulna were 3°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…However, no specific treatment modality has been described yet 9 , 12 14 . Surgeons usually rely on osseous changes on X-ray and three dimensional (3D) computed tomography (CT) for surgical treatment 15 , 16 . Available classification systems such as Cleary & Omer and Tachdjian classification also mainly discuss on radiographic abnormality 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…However, no specific treatment modality has been described yet 9 , 12 14 . Surgeons usually rely on osseous changes on X-ray and three dimensional (3D) computed tomography (CT) for surgical treatment 15 , 16 . Available classification systems such as Cleary & Omer and Tachdjian classification also mainly discuss on radiographic abnormality 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [11][12][13] have shown that the deformity of the CRUS forearm is complex, which consists of several independent deformities, including radial deformities, ulnar deformities, deformities at the proximal part of radius and ulna, and the deformities at the distal part of radius and ulna, among others. These independent deformities, such as radial and ulnar deformities, are associated with the severity of xed forearm rotation deformity.…”
Section: Discussionmentioning
confidence: 99%
“…Digital model reconstruction software was used to conduct digital 3-D modeling using the DICOM les of forearm CT. The independent osseous deformities of CRUS were as follows [11][12][13] : 1) the radial diaphysis is in an arch shape, and its deformity is characterized by internal rotation, radial, and dorsal angulations;…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with congenital hand malformations, preoperative assessment is mostly performed with plain X-rays, which can detect almost all bone malformations, but is limited in depiction of growth plates and cartilaginous structures. A computer tomographic (CT) scan can show more complex changes in bones and joints (Nakasone et al., 2018); and three-dimensional (3-D) CT angiography is noninvasive and is widely used in preoperative planning for microsurgical reconstruction in evaluating both donor and recipient vascular supply (Chen et al., 2016; Duymaz et al., 2009). Three-dimensional CT angiography can be a helpful tool in surgical decision making for congenital hand malformations (Askari et al., 2016; Holten et al., 1997a; Kilinc et al., 2018), but it still does not see routine use.…”
Section: Introductionmentioning
confidence: 99%